A Preliminary Exploration of Factors Affecting a University Entrepreneurship Ecosystem - Wang, Xuyan; Sun, Xiaoyang; Liu, Shuhua; Mu, Chen (Frontiers in Psychology, 2021)
This article examines the factors that affect the formation and operation of the university entrepreneurship ecosystem. Employing case-study methodology, this research attempts to provide evidence-based analysis of the existing theoretical framework of university entrepreneurship ecosystem and verify the role of elements in it through empirical experience as described in semi-structured interviews with 33 respondents on and off an American university. Findings reveal that extracurricular activities, networks, entrepreneurial culture and leadership have important impact on the formation and operation of the university entrepreneurship ecosystem. Specifically, compared with formal courses, as important carriers, extracurricular activities have more positive impact on students’ entrepreneurship. Different levels of networks can promote the circulation and exchange of resources. Culture is an important factor in forming and promoting individual entrepreneurial behavior and their agglomeration in the university entrepreneurship ecosystem. Clear vision and long-term commitments to entrepreneurship, namely the leadership, play a leading role in the formation and development of a university entrepreneurship ecosystem.